Benzothiadiazole enhances ascorbate recycling and polyphenols accumulation in blueberry in a cultivar-dependent manner - Cocetta, Giacomo; Cavenago, Beatrice; Bulgari, Roberta; Spinardi, Anna (Frontiers in Plant Science, 2022)
Benzothiadiazole (BTH) is a functional analogue of salicylic acid able to induce systemic acquired resistance in many horticultural crops. The aim of the work was to investigate how BTH may affect i) fruit quality, ii) ascorbic acid (AsA) oxidation and recycling metabolism and iii) phenolic compounds accumulation, during development and ripening of berries from the two selected cultivars. Blueberry (Vaccinium corymbosum L.) plants (cv 'Brigitta' and 'Duke') were treated with 0.118 mM BTH every two weeks during ripening, then all fruits of each plant were harvested and divided in four developmental stages. Results indicated that BTH had no marked effects on fruit quality parameters. During the first developmental stage, BTH negatively affected dry matter in both cv, while soluble solids and AsA content were affected in ‘Duke’. In fully ripe berries, BTH reduced dry matter in ‘Duke’ and enhanced soluble solids content in ‘Brigitta’, while diminishing titratable acidity. AsA content was positively affected by BTH in ‘Duke’, but not in ‘Brigitta’. The effect of BTH on the enzymes involved in AsA recycling was recorded in berries at the third (fruit more than half pigmented) and fourth developmental stages. After treatment, in both cv ascorbate peroxidase (APX) activity increased in fully ripe berries, while monodehydroascorbate reductase (MDHAR) activity was stimulated at the third ripening stage. Conversely, the activities of dehydroascorbate reductase (DHAR) and glutathione reductase (GR) were enhanced only in ‘Brigitta’ and in ‘Duke’, respectively. BTH stimulated total phenols, flavonoid and anthocyanin accumulation in ‘Brigitta’ and in ‘Duke’ at the third and fourth ripening stages. In fully ripe berries, BTH enhanced the accumulation of delphinidins, cyanidins, petunidins and peonidins in ‘Brigitta’, while in ‘Duke’ it increased all classes of anthocyanidins, including malvidin. On the contrary, the relative proportion of the individual anthocyanins was only slightly affected by BTH treatment, mainly regarding delphinidin and malvidin at the third and fourth stage of ripening of ‘Duke’ and ‘Brigitta’, respectively. These results show that preharvest BTH application can positively impact on fruit bioactive compounds levels, affecting AsA recycling and content and increasing phenolic accumulation in fruit, but partly depending on cv and ripening stage.